2003
DOI: 10.1093/genetics/163.1.453
|View full text |Cite
|
Sign up to set email alerts
|

Mosaicism of Solid Gold Supports the Causality of a Noncoding A-to-G Transition in the Determinism of the Callipyge Phenotype

Abstract: To identify the callipyge mutation, we have resequenced 184 kb spanning the DLK1-, GTL2-, PEG11-, and MEG8-imprinted domain and have identified an A-to-G transition in a highly conserved dodecamer motif between DLK1 and GTL2. This was the only difference found between the callipyge (CLPG) allele and a phylogenetically closely related wild-type allele. We report that this SNP is in perfect association with the callipyge genotype. The demonstration that Solid Gold—the alleged founder ram of the callipyge flock—i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(13 citation statements)
references
References 8 publications
0
12
0
1
Order By: Relevance
“…The mutation has not altered the imprinting status of these genes, but their expression in the hypertrophy responsive muscles has changed in a manner that is generally consistent with the parent-of-origin-specific inheritance of the mutation on the maternal or paternal chromosome (cis effect) (Charlier et al, 2001a(Charlier et al, , 2001b. The callipyge mutation occurs in a 12-bp motif that was identical in 13 mammalian species with the exception of descendants of Solid Gold (Smit et al, 2003). The cis effect of the callipyge allele affects both genes and bidirectional intergenic transcription across approximately 300 kb of the chromosome, and therefore, the sequence surrounding the mutation was considered to be a long-range control element {Charlier, 2001 #55; Takeda, 2006 #410}.…”
Section: Epigenetic Changes At the Site Of The Callipyge Mutationmentioning
confidence: 70%
See 1 more Smart Citation
“…The mutation has not altered the imprinting status of these genes, but their expression in the hypertrophy responsive muscles has changed in a manner that is generally consistent with the parent-of-origin-specific inheritance of the mutation on the maternal or paternal chromosome (cis effect) (Charlier et al, 2001a(Charlier et al, , 2001b. The callipyge mutation occurs in a 12-bp motif that was identical in 13 mammalian species with the exception of descendants of Solid Gold (Smit et al, 2003). The cis effect of the callipyge allele affects both genes and bidirectional intergenic transcription across approximately 300 kb of the chromosome, and therefore, the sequence surrounding the mutation was considered to be a long-range control element {Charlier, 2001 #55; Takeda, 2006 #410}.…”
Section: Epigenetic Changes At the Site Of The Callipyge Mutationmentioning
confidence: 70%
“…A single base change of an A (wild-type allele: +) to a G (callipyge allele: C) in the intergenic region between DLK1 and Maternal Expressed Gene 3 (MEG3) has been shown to be 100% concordant with all animals of the +/C P genotype and unique to direct descendants of the founder ram "Solid Gold" . Solid Gold was found to be mosaic for the mutation (Smit et al, 2003), providing strong evidence that the single-nucleotide polymorphism is the causative mutation. Preliminary expression analysis found an ncRNA (CLPG1) that spans the region containing the single-nucleotide polymorphism in neonatal longissimus dorsi RNA .…”
Section: The Callipyge Mutationmentioning
confidence: 99%
“…Imprinted genes which show parent-of-origin expression manner have been detected in mammals, plants and insects (Ferguson-Smith, 2011). The most famous imprinted genes in livestock are the callipyge mutation in sheep (Smit et al, 2003) and the IGF2 gene in pigs (Jeon et al, 1999). In livestock, for the first time, de Vries et al (1994) studied the contribution of parent-of-origin effects to carcass and growth traits in pigs.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, DLK1 has been widely studied in sheep for the diagnosis of the Single Nucleotide Polymorphism (SNP) for the CLPG phenotype ( Cockett et al., 1996 ). Smit et al. (2003) have studied DLK1 expression in the CLPG phenotype and as a result, they have shown that the expression level of DLK1 enhanced.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the important role of DLK1 in muscle and its association with the CLPG phenotype in sheep, it is an important candidate gene in marker-assisted selection. However, the mutation in CLPG, which is breed-specific, is only seen in callipyge herds ( Smit et al., 2003 ). In a previous study, Kim et al.…”
Section: Introductionmentioning
confidence: 99%